Heterogeneous Transition-Metal-Free Alcohol Oxidation by Graphene Oxide Supported Iodoxybenzoic Acid in Water - Kim, Yo-Han; Jang, Hyung-Seok; Kim, Young-O; Ahn, So-Dam; Yeo, Sewon; Lee, Sang-Myung; Lee, Yoon-Sik (Synlett, 2013)
The metal-free oxidation of organic compounds is one of the most demanding reactions in chemical industries. As such, iodoxybenzoic acid (IBX) is an attractive reagent due to its metal-free oxidative activity. To apply IBX for the alcohol oxidation in water, IBX was immobilized on graphene oxide (GO). GO-supported IBX reagent exhibited excellent performance for alcohol oxidation reaction in water with greater than 90% selectivity. It could be reused without significant loss of oxidative activity.
Keywords: graphene oxide; iodoxybenzoic acid; alcohol oxidation; water-based system